ANALISA PENGARUH PELATIHAN MEDIA PEMBELAJARAN ONLINE PADA GURU SEKOLAH DASAR NEGERI 2 KAWAN BANGLI - Ni Ketut Utami Nilawati; Ayu Manik Dirgayusari; I Kadek Dwi Gandika Supartha; Dewa Putu Yudhi Ardiana; I Gde Eka Dharsika (PUAN INDONESIA, 2022)
With the current outbreak of the corona virus, all sectors must start to improve so that they can survive during a pandemic, including the education sector. The teaching and learning process carried out during a pandemic situation like this is carried out using an online system and distance learning. Teachers must be able to provide facilities so that students can absorb the material optimally. Another problem that arises is that not all teachers are able to implement the distance learning system and also using the applications or technologies that support distance learning system. To solve this problem, the school needs to get the training of how to make a distance learning system media and in this case the school cooperates with STMIK STIKOM INDONESIA (STIKI) for the training. The training materials provided are google classroom training, google form and training on making the learning videos. The results of the analysis were obtained from the pretest and posttest questionnaires which were described descriptively. After receiving the training, most of the teachers will switch to use the Google Classroom media instead of WA social media, because 100% of the teachers stated that Google Classroom is very helpful in supporting online learning. In addition, according to the posttest questionnaires, 8.3% of the teachers understand very well about the features contained in Google Classroom, 41.7% understand it well and 50% are understand it quite well, meaning that most of the teachers understand the use of Google Classroom. The training also received a good responses from SDN 2 Kawan School and it will be applied to support their distance learning system.